2003
DOI: 10.1063/1.1622441
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of near-ultraviolet InGaN/GaN light-emitting diodes by inserting an in situ rough SiNx interlayer in n-GaN layers

Abstract: Near-ultraviolet 400-nm InGaN/GaN multiple-quantum-well light-emitting diodes (LEDs) with and without an in situ rough SiNx interlayer inserted into the n-GaN underlying layer were grown on c-face sapphire substrates by metalorganic vapor phase epitaxy. Inserting the SiNx interlayer into the n-GaN underlying layer slightly reduced leakage current induced by reducing the defect density. Additionally, an enhancement of light extraction for the LED with a SiNx interlayer is expected because of the increased inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…It was found that the TD density can be lowered one order of magnitude than the conventional UVLED by inserting the SiN buffer layer. The density of dislocations is remarkably lower in GaN layers grown after SiN buffer than the density in layers obtained using the conventional process [13][14][15]. Fig.…”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…It was found that the TD density can be lowered one order of magnitude than the conventional UVLED by inserting the SiN buffer layer. The density of dislocations is remarkably lower in GaN layers grown after SiN buffer than the density in layers obtained using the conventional process [13][14][15]. Fig.…”
Section: Methodsmentioning
confidence: 87%
“…However, such a procedure is relatively complex that inevitably results in a low production yield. Recently, it has been reported that one can reduce the defect density in nitride-based epitaxial layers using GaN-SiN as the nucleation layer [8][9][10][11][12][13][14][15]. Many nanometer-sized porous SiN layer probably serves to enhance the lateral growth, which is quite similar to that in ELO to reduce dislocation density.…”
Section: Introductionmentioning
confidence: 95%
“…Similar works were performed for light emitting diodes (LEDs) and thin-film electroluminescence (TFEL) devices. High light extraction efficiency could be obtained by surface texturing [12], surface roughing [13], a two-dimensional surface grating [14], inserting an in situ rough SiN x [15], and introducing a two-dimensional SiO 2 nanorod pattern into the glass substrate of a TFEL [16].…”
Section: Introductionmentioning
confidence: 99%
“…The FWHM of the D 0 X peak obtained from Gaussian fits is around 4 meV, indicating high optical quality of the overgrowth GaN film. As discussed in the recent work [8][9][10], the higher intensity may be used to random scattering of the light at a rough interface between the overgrown GaN and the SiO 2 over that from the interface between GaN and sapphire substrate.…”
Section: Contributed Articlementioning
confidence: 96%